A New Evaluation Method of Total Organic Carbon for Shale Source Rock Based on the Effective Medium Conductivity Theory. (27th October 2021) - Fu, Jian; Li, Xuesong; Sun, Yonghe; Huo, Qiuli; Gao, Ting; Fu, Li; Liu, Yuchen; Dong, Suxing; Fan, Haijun
Abstract : In the evaluation of source rocks, the total organic carbon (TOC) is an important indicator to evaluate the hydrocarbon generation potential of source rocks. At present, the commonly used methods for assessing TOC include △ log R and neural network method. However, practice shows that these methods have limitations in the application of unconventional intervals of sand-shale interbeds, and they cannot sufficiently reflect the variation of TOC in the vertical direction. Therefore, a total organic carbon (TOC) evaluation model suitable for shale and tight sandstone was established based on the effective medium symmetrical conduction theory. The model consists of four components: nonconductive matrix particles, clay minerals, organic components (solid organic matter and hydrocarbons), and pore water. The conductive phase in the model includes clay minerals and pore water, and other components are treated as nonconductive phases. When describing the conductivity of rock, each component in the model is completely symmetrical, and anisotropic characteristics of each component are considered. The model parameters are determined through the optimization method, and the bisection iteration method is used to solve the model equation. Compared with the classic TOC calculation method, the new model can evaluate the abundance of organic matter in shale and tight sandstone, which provides a new option to assess the TOC of rocks based on logging methods.